Applicability of a coastal morphodynamic model for fluvial environments. (June 2016) - Beevers, Lindsay; Popescu, Ioana; Pan, Quan; Pender, Douglas
Abstract: The dominant processes of sediment transport and morphological changes are different between rivers and coastal areas. In many situations rivers, estuaries and coasts need to be modelled together in an integrated way. This paper investigates the capability of a freely available, open source, coastal morphodynamic software (XBeach) to estimate sediment transport and morphological changes in fluvial environments. Four benchmark tests were designed to test code performance and included simple unidirectional flow cases, complex topography, fluvial flood flows (hydrographs) and dam break scenarios (fast transient, supercritical flow fields). The results were compared to laboratory experimental results or simulations results from industry standard software. Analysis suggested that the coastal morphodynamic code is able to simulate sediment transport and morphological changes in a fluvial environment, but there are limitations to what can be modelled and the accuracy to which they are modelled. General morphological trends are replicated reasonably well by the code however specific bed forms and rapid erosive responses are less well modelled. Suggestions are made for applicability of the code, code improvement and future work. Highlights: Evaluation of XBeach numerical scheme in fluvial environments. Benchmarking of the code to laboratory experimental results (flume and dam break). Discussion of code performance in fluvial and transitional (estuarine) environments.